Determinación de la prevalencia de brucelosis bovina (Brucella abortus) en la provincia de Manabí mediante la prueba de la rosa bengala. - Arias Caisaguano, Gustavo Ulices (2013)
The present research was conducted on bovine brucellosis in the province of Manabí and analysis would run in the Biotechnology Laboratory of State Technical University Quevedo the overall objective of this research was to determine the percentage of Brucella abortus in cattle Creole in the Manabí province by the serological Rose Bengal. In this study we stipulate the percentage of bovine brucellosis in the Creole and European historical prevalence in herds and also determined the sensitivity and specificity of the Rose Bengal (RB). To determine the degree of prevalence of brucellosis, we sampled a total of 334 cattle (167 European and 167 native), positivism was reached, 19 (11.37%), 148 (88.63%) negative, but not in the European race which was 30 (17.96%) of positive, 137 (82.04%) were negative. The test revealed a Rose Bengal (14.63% sensitivity and 85.37% specificity). The results show that the detection of positive animals by Rose Bengal test was specific and sensitive, so the test can be a useful tool in the diagnosis of Brucella abortus and eradication program. There remains the risk of human brucellosis in the province in the presence of cattle infected with the disease and if no action is taken may become infected by consuming milk and dairy product pausterizado bad. Finally we analyzed the economic losses per cow that aborts which was $ 520.